Feline Respiratory Extramedullary Plasmacytoma with Lymph Node Metastasis and Intrahistiocytic Amyloid. Issue 2 (February 2017) - Sykes, S.E.; Byfield, V.; Sullivan, L.; Bender, S.J.; Moore, P.F.; Sánchez, M.D.
Summary: A 14-year-old domestic longhaired cat presented with a 2-year history of nasal discharge and a recent onset of inappetence and submandibular lymphadenopathy. The cat was humanely destroyed after developing severe respiratory distress. Necropsy examination revealed thickened nasal turbinates and soft palate, and friable red–tan material within the frontal sinus, nasal cavity and nasopharynx. The lungs contained multifocal irregular friable tan nodules. Multiple lymph nodes were enlarged, friable and red–tan in colour. Histopathology revealed a mature type extramedullary plasmacytoma (EMP) within the frontal sinus, nasal cavity, soft palate, larynx, trachea, lungs and multiple lymph nodes. The lymph nodes and larynx also contained marked granulomatous inflammation with extensive intrahistiocytic (and lesser amounts of extracellular) lambda light chain amyloid, confirmed by electron microscopy and immunohistochemistry. Neoplastic cells expressed CD79a and MUM1. This is the first report of an infiltrative EMP of the feline respiratory tract with lymph node metastasis and predominantly intrahistiocytic amyloid.